Can Social Security Be Saved? - Dimitri B. Papadimitriou; L. Randall Wray (Levy Economics Institute of Bard College, 1999)
The first part of this paper is an overview of projections of Social Security's future and an explanation of why the projections have led many to believe there is a looming financial crisis. We argue that any problems to be faced are far down the road and not severe enough to justify the use of the word "crisis." Something will have to be done to resolve the real and financial problems that are likely to crop up in two or three decades. However, this does not in itself mean that something has to be done today specifically to save Social Security. The second part of the paper discusses the real and financial nature of Social Security's problems. Almost all commentators have focused on the financing of Social Security and thus have proposed financial solutions. We argue that the questions about the future of Social Security concern the size and distribution of the real economic pie. Once this is recognized, it becomes obvious that none of the popular reforms, such as privatization, reduction of current benefits, and President Clinton's proposal to "set aside" budget surpluses, can really help. We conclude with alternative policy recommendations that are consistent with the true nature of the future problem.
Keywords: 330